Gallium arsenide nanowires formed by Au - assisted metal - organic chemical vapor deposition : effect of growth temperature - Rosnita Muhammad, 1972-, author; Zulkafli Othaman, author; Yussof Wahab, author; Samsudi Sakrani, author; Wan Faizal Wan Ahmad, author; Mohd. Nazri, author (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL